Accountability And Transparency In Grogol Village Fund Management, Karangtendah District, Demak Regency - C Susmono Widagdo; Lis Widowati; Rahayu Setia Wati (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Accountability is the government's responsibility to report and present activities that have been carried out to the public. This accountability is carried out so that the government can be transparent with the commitments that have been formed in its implementation. The Grogol Village Government, Karangtengah District, Demak Regency is a Village Government that supports Good Governance, especially accountability and transparency. This research aims to assess the accountability and transparency of the Village Government regarding the management of Village Funds in Grogol Village, Karangtengah District, Demak Regency. This research uses a qualitative method based on field studies. The data collection technique used was an interview with a semi-structured technique. Interviews were conducted with the Village Government which carries out government administration and the Village Consultative Body (BPD) as representatives of the community, totaling 9 informants. The results of this research show that the financial management of Village Funds implemented by the Grogol Village Government is in accordance with applicable laws and regulations. The transparency carried out by the Grogol Village Government uses digital information media, information is disseminated by each village through the RT head and RW head, apart from that there is also an information board placed at the Village Office. Even though the management of Village Funds carried out by the Village Government is very good, community understanding of Village Fund policies is still low.